2018
DOI: 10.5765/jkacap.2018.29.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Early Trauma Inventory Self Report-Short Form among Korean Adolescents

Abstract: Objectives: Experiencing early childhood trauma is related to multiple psychiatric problems in adolescents and adulthood. This study aimed to examine the reliability and validity of the Korean version of the Early Trauma Inventory Self Report-Short Form (ETISR-SF) among Korean adolescents. Methods: A total of 86 adolescents aged 12-17 years (mean age 14.50±1.35 years, range 12-17) were assessed using the ETISR-SF. Other instruments, including the Children's Depression Inventory (CDI), the revised Children's Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
8
1
Order By: Relevance
“…Consistent with prior findings on the high prevalence of traumatic experiences in refugee populations [ 39 , 40 ], and specifically among North Korean refugees (for a review, [ 26 ]), our findings showed a high frequency of early traumatic experiences among North Korean adolescents and young adults. In comparison with healthy South Korean adolescent and adult samples from previous studies [ 29 , 41 ], young North Korean refugees in this study had a generally higher number of early traumatic events that had ever occurred (5.99 vs. 2.33–3.65). Specifically, the average number of general traumatic events and experiences of sexual abuse they had experienced (2.13, 0.36 respectively) was more than twice higher than that of Korean adolescents and adults (0.86–0.96, 0.13–0.17, respectively) and the number of instances of physical abuse and emotional abuse they had ever experienced (2.11, 1.39, respectively) also tends to be higher than that in the Korean samples (0.80–1.79, 0.54–0.74, respectively).…”
Section: Discussioncontrasting
confidence: 59%
“…Consistent with prior findings on the high prevalence of traumatic experiences in refugee populations [ 39 , 40 ], and specifically among North Korean refugees (for a review, [ 26 ]), our findings showed a high frequency of early traumatic experiences among North Korean adolescents and young adults. In comparison with healthy South Korean adolescent and adult samples from previous studies [ 29 , 41 ], young North Korean refugees in this study had a generally higher number of early traumatic events that had ever occurred (5.99 vs. 2.33–3.65). Specifically, the average number of general traumatic events and experiences of sexual abuse they had experienced (2.13, 0.36 respectively) was more than twice higher than that of Korean adolescents and adults (0.86–0.96, 0.13–0.17, respectively) and the number of instances of physical abuse and emotional abuse they had ever experienced (2.11, 1.39, respectively) also tends to be higher than that in the Korean samples (0.80–1.79, 0.54–0.74, respectively).…”
Section: Discussioncontrasting
confidence: 59%
“…For this reason, sexual abuse is likely to be underestimated. Findings related to this domain have had low reliability in previous studies [ 39 , 40 ]. Each item was answered “yes” or “no” and scored dichotomously (yes = 1/no = 0) [ 39 , 41 ].…”
Section: Methodsmentioning
confidence: 88%
“…Findings related to this domain have had low reliability in previous studies [ 39 , 40 ]. Each item was answered “yes” or “no” and scored dichotomously (yes = 1/no = 0) [ 39 , 41 ]. We conducted confirmatory factor analysis (CFA) for the present sample, and items with factor loadings below 0.50 were excluded from the analysis.…”
Section: Methodsmentioning
confidence: 88%
“…This inventory consisted of 27 questionnaires covering four subsets of adversities: general, physical, emotional, and sexual adversities. A standardization study proved its validity and internal consistency [ 12 , 13 ]. The adversities were quantitatively assessed and analyzed.…”
Section: Methodsmentioning
confidence: 99%